Vegetation turnover in a braided river: frequency and effectiveness of floods of different magnitude. Issue 4 (22nd October 2014) - Surian, Nicola; Barban, Matteo; Ziliani, Luca; Monegato, Giovanni; Bertoldi, Walter; Comiti, Francesco
Abstract This work addresses the temporal dynamics of riparian vegetation in large braided rivers, exploring the relationship between vegetation erosion and flood magnitude. In particular, it investigates the existence of a threshold discharge, or a range of discharges, above which erosion of vegetated patches within the channel occurs. The research was conducted on a 14 km long reach of the Tagliamento River, a braided river in north‐eastern Italy. Ten sets of aerial photographs were used to investigate vegetation dynamics in the period 1954–2011. By using different geographic information system (GIS) procedures, three aspects of geomorphic‐vegetation dynamics and interactions were addressed: (i) long‐term (1954–2011) channel evolution and vegetation dynamics; (ii) the relationship between vegetation erosion/establishment and flow regime; (iii) vegetation turnover, in the period 1986–2011. Results show that vegetation turnover is remarkably rapid in the study reach with 50% of in‐channel vegetation persisting for less than 5–6 years and only 10% of vegetation persisting for more than 18–19 years. The analysis shows that significant vegetation erosion is determined by relatively frequent floods, i.e. floods with a recurrence interval of c. 1–2.5 years, although some differences exist between sub‐reaches with different densities of vegetation cover. These findings suggest that the erosion of riparian vegetation in braided rivers may not be controlled solely by very large floods, as is the case for lower energy gravel‐bed rivers. Besides flow regime, other factors seem to play a significant role for in‐channel vegetation cover over long time spans. In particular, erosion of marginal vegetation, which supplies large wood elements to the channel, increased notably over the study period and was an important factor for in‐channel vegetation trends. Copyright © 2014 John Wiley & Sons, Ltd.